National industrial policy : a strategic plan for growth and development (Jamaica Information Service KingstonJM, 1996)
Seeks to provide the necessary basis for a clear, coherent and consistent set of policies to guide the Jamaican economy on a path of renewed growth and development.
Additional copy located in the Office of the Secretary-General